Physicians’ attitudes towards disclosure of payments from pharmaceutical companies in a nationwide voluntary transparency database: a cross-sectional survey - Marlene Stoll; Lara Hubenschmid; Cora Koch; Klaus Lieb; Boris Egloff (BMJ Open)
Objectives To investigate German physicians’ attitudes towards and experiences with voluntary disclosure of payments by pharmaceutical companies in a public database and their impact on future decisions for or against disclosure.Design A national cross-sectional survey conducted in 2018 among physicians who voluntarily disclosed at least one payment in the German transparency regulation.Setting Retrospective paper-pencil questionnaire about attitudes towards and experiences with voluntary payment disclosures in the first (2015) and second (2016) years of the German transparency regulation.Participants German physicians who disclosed either in the first year only, the second year only, or in both years of the transparency regulation.Primary outcomes (1) The probability to disclose in 2016, predicted by physicians’ experience of reactions from others in 2015, descriptive norms and attitudes towards transparency; (2) Frequency and (3) Content of reactions from others in 2015 compared with 2016.Results Data of 234 respondents were analysed (n=42, 45 and 147 physicians who disclosed in 2015, 2016 or both years, respectively). The probability to disclose in 2016 was not predicted by perceived reactions, norms or attitudes towards transparency (p>0.01). Most participants reported not to have received any reactions by patients (190/234, 81%), colleagues (128/234, 55%) or the private environment (153/234, 65%). Neither frequency nor content of reactions differed between the first and second years (scale 1–5; frequency: Mdn2015,2016 = 1.33 vs 1.00, rb=−0.17, p>0.01; content: Mdn2015,2016 = 3.00 vs 3.00, rb=0.19, p>0.01). However, media reporting, fear of reputational damage and a feeling of being defamed were mentioned as reasons for non-disclosure.Conclusions While confirmatory analyses did not provide significant results, descriptive analyses showed that participants who voluntarily disclose payments mainly do not experience any reactions towards their disclosures but report fears about losing their reputation due to disclosures.